Development and validation of a nomogram to predict drainage duration in patients with breast cancer treated with modified radical mastectomy - Song Wu (Nature Portfolio, 2021)
Abstract Appropriate drainage duration is vital for the postoperative rehabilitation of patients with breast cancer (BC) undergoing modified radical mastectomy (MRM). To provide better and individualized postoperative management for these patients, this study explored independent predictors of postoperative drainage duration in patients with BC. This was a single-center retrospective cohort study. Patients diagnosed with BC and treated with MRM from May 2016 to April 2020 were randomly divided into training (n = 729) and validation (n = 243) cohorts. Univariate and multivariate Cox analyses revealed that the body mass index, serum albumin level, hypertension, number of total dissected axillary lymph nodes, and ratio of positive axillary lymph nodes were independent predictors of postoperative drainage duration in the training cohort. Based on independent predictors, a nomogram was constructed to predict the median postoperative drainage duration and the probability of retaining the suction drain during this period. This nomogram had good concordance and discrimination both in the training and validation cohorts and could effectively predict the probability of retaining the suction drain during drainage, thus assisting clinicians in predicting postoperative drainage duration and providing individualized postoperative management for patients with BC.